2008
DOI: 10.1590/s1806-83242008000400006
|View full text |Cite
|
Sign up to set email alerts
|

Professional flossing as a diagnostic method for gingivitis in the primary dentition

Abstract: The aim of this study was to evaluate flossing as a diagnostic method for interproximal gingival bleeding in children. For this crossover study, 23 pre-schoolchildren presenting neither restorations nor approximal carious cavities and with at least 15% of gingival bleeding sites were selected. Examinations were performed at three different moments (3-4 days interval). Examinations comprised repeated measurements of two gingival indices with a 10-minute interval in the following sequences: the Ainamo & Bay Ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
5
2
1
Order By: Relevance
“…By reversing the order of the assessments, in the first flossing-second GBI group, lower S values and higher SP values were observed; however, there was a larger number of false positives than false negatives. These findings are not in agreement with those of Mariath et al, 16 who found low S values and high SP values for the first GBI-second flossing and first floss-second GBI groups. These differences may be explained, in part, by the fact that children were evaluated in the study of Mariath et al 16 Gingivitis is less severe in children compared to adults, when similar amounts of dental plaque are found.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…By reversing the order of the assessments, in the first flossing-second GBI group, lower S values and higher SP values were observed; however, there was a larger number of false positives than false negatives. These findings are not in agreement with those of Mariath et al, 16 who found low S values and high SP values for the first GBI-second flossing and first floss-second GBI groups. These differences may be explained, in part, by the fact that children were evaluated in the study of Mariath et al 16 Gingivitis is less severe in children compared to adults, when similar amounts of dental plaque are found.…”
Section: Discussioncontrasting
confidence: 99%
“…9,15,16 In the present study, flossing against the teeth was compared with that against the gums. In the absence of bleeding with TF in the first assessment, 19% of the sites bled following the second assessment with GF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations